An in vitro and in vivo Comparison of the Effect of Stevia rebaudiana Extracts on Different Caries-Related Variables: A Randomized Controlled Trial Pilot Study - Brambilla, E.; Cagetti, M.G.; Ionescu, A.; Campus, G.; Lingström, P. (Caries research, 2014)
The effect of Stevia extracts on in vitro Streptococcus mutans biofilm formation and in vivo plaque pH was evaluated in this paper. Three 10% solutions containing stevioside, rebaudioside A or sucrose were prepared. MTT assay was used to evaluate microbiological counts in vitro. Twenty volunteers rinsed for 1 min with each solutions, and plaque pH was measured at 7 time points after each rinse. Higher in vitro S. mutans biofilm formation was observed in sucrose solution (p < 0.01). After 5, 10, 15 and 30 min, the sucrose in vivo rinse produced a statistically significantly lower pH value compared to the Stevia extracts (F = 99.45, p < 0.01).Stevia extracts can be considered nonacidogenic.